High IDO‐1 expression in tumor endothelial cells is associated with response to immunotherapy in metastatic renal cell carcinoma. Issue 5 (16th April 2018) - Seeber, Andreas; Klinglmair, Gerald; Fritz, Josef; Steinkohl, Fabian; Zimmer, Kai‐Christian; Aigner, Friedrich; Horninger, Wolfgang; Gastl, Günther; Zelger, Bettina; Brunner, Andrea; Pichler, Renate
Abstract : Nivolumab belongs to the standard therapy in the second‐line setting of metastatic renal cell carcinoma (mRCC). Although deep and long‐lasting responses are seen in some patients, the majority of patients will further progress. PD‐L1 is still under critical evaluation as a predictive biomarker. Thus, more accurate biomarkers are clearly warranted. Here, we investigated for the first time the predictive role of IDO‐1, a negative immune‐regulatory molecule, on clear cell RCC tissues of 15 patients undergoing nivolumab therapy. IDO‐1 and other immune inhibitory molecules (PD‐L1, PD‐L2, FOXP3) as well as immune cell subsets (CD3, CD4 and CD8) were measured on formalin‐fixed, paraffin‐embedded sections of RCC specimens by immunohistochemistry. IDO‐1 was predominantly expressed in tumor endothelial cells, and was totally absent from tumor cells itself. IDO‐1 overexpression (>10%) could be detected more frequently in responders (100%, n = 6/6) compared to non‐responders (33.3%, n = 3/9; P = .028), resulting in a better progression‐free survival during immunotherapy (IDO‐1 ≤ 10% vs >10%, median: 3.5 vs not estimated (NE) months, P = .01 by log‐rank test). In addition, IDO‐1 was positively correlated with CD8 + T cell expression ( r s = .691, P = .006). PD‐L1 expression on tumor cells was negative in 13 (86.7%) of 15 patients, irrespective of therapeutic response (responders vs non‐responders: 83.3% vs 88.9%). No differences were noticed in the PD‐L1 expression on tumor‐infiltrating immune cells (PD‐L1 < 1% in 66.7% of both responders and non‐responders). In contrast to PD‐L1, these results suggest that IDO‐1 may be a more promising predictive biomarker for response to immune‐based cancer therapy in mRCC. Abstract : In this retrospective study, we analyzed the predictive value ot the expression of IDO1 on tumor tissue of renal cell carcinoma patients undergoing checkpoint inhibition. A signifcanty correlation between the overexpression of IDO1 in tumor endothelial cells and response to nivolumab therapy could be found for the first time.